Comparison of Demographic Characteristics of Complete Edentulism Cases - Basnet, Bishal Babu; Limbu, Indra Kumar; Parajuli, Prakash Kumar (Journal of Nepal Health Research Council, 2025)
Background: Complete edentulism is terminal outcome of tooth loss which itself is multifactorial entity. The periodic comparison of demographic variables in the complete edentulous cases attending dental hospital can give an insight into the status of oral health care, awareness of dental treatment and burden of disease in the community.Methods: This is a hospital-based study on secondary data of all the cases attending for complete denture therapy from January to December of three years viz. 2012, 2017 and 2022. Proportion of gender, age-specific distribution, geographic residence of patients is presented in percentage. The mean age of patients among three years is compared using One-way ANOVA at 95% confidence interval at level of significance at 0.05.Results: A data of 830 patients were extracted for analysis. The demographic parameters were obtained and analysed using SPSS 11.5. In all years, male and female patients were almost equal. The number of patients has increased markedly from 2012 to 2017 but plateaued towards 2022. The mean age of patients being edentulous (65.71±10.38 years in 2012, 66.44±8.75 years in 2012 and 66.38±8.83 years in 2022) has not changed significantly (p >0.05) over ten years.Conclusions: In ten years’ time, demand of conventional complete denture has slightly increased, mean age of edentulism remained stagnant and patients from remote hill areas had to visit faraway hospitals for denture therapy. Large scale studies in community are needed to find out the disease burden and determinants of complete edentulism in Nepalese population. Keywords: Complete denture; dental care; edentulism; oral health